2012
DOI: 10.3390/molecules17055385
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging, Antimicrobial and Immunomodulatory Activities of Orthosiphon stamineus

Abstract: Received : 12 March 2012; in revised form: 10 April 2012 / Accepted: 17 April 2012 / Published: 8 May 2012 Abstract: Orthosiphon stamineus is considered an important traditional folk medicine. In this study ethanol and aqueous extracts of O. stamineus were evaluated in vitro for their antioxidant, antimicrobial as well as for their immunomodulatory properties on human peripheral blood mononuclear cells (PBMCs). The DPPH radical scavenging method was used for the determination of antioxidant activity, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 25 publications
0
37
1
2
Order By: Relevance
“…The lowest MIC value was seen for S. aureus (12.5 mg/mL for methanol extract and 6.25 mg/mL for aqueous extract). Alshawsh (2012), showed that the lowest MIC value of O. stamineus leaf extract at 1.56 mg/mL while in this present study, the aqueous extract from the whole plant showed the lowest MIC value of 6.25 mg/mL. The antibacterial activity in their study is higher compared to this study because different part of the plant was used.…”
Section: Determination Of Mic Value Of Ostamineus Extractscontrasting
confidence: 46%
“…The lowest MIC value was seen for S. aureus (12.5 mg/mL for methanol extract and 6.25 mg/mL for aqueous extract). Alshawsh (2012), showed that the lowest MIC value of O. stamineus leaf extract at 1.56 mg/mL while in this present study, the aqueous extract from the whole plant showed the lowest MIC value of 6.25 mg/mL. The antibacterial activity in their study is higher compared to this study because different part of the plant was used.…”
Section: Determination Of Mic Value Of Ostamineus Extractscontrasting
confidence: 46%
“…The O. stamineus extract used in this study was more in a crude form, which may explain its low antibacterial activity. Previous studies which reported the protective effects of O. stamineus employed methanolic (Chun-Hoong et al, 2010;Malahubban et al, 2013) and ethanolic extracts (Alshawsh et al, 2012;Mohamed et al, 2012).…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%
“…Studies on the antimicrobial activity of O. stamineus have been reported against Staphylococcus aureus, Streptococcus agalactiae and Vibrio parahemolyticus (Ho et al, 2010;Mohammed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…5) was isolated from the roots of C. robustum, which is used as a traditional Chinese medicine to treat external injuries and irregular menses, and showed good scavenging effects against DPPH radicals with an IC 50 value of 39 µM. 58) Furthermore, numerous extracts from TMPs showed marked antioxidant activity, such as Kleinhovia hospita, 59) Orthosiphon stamineus, 60) Anogeissus acuminata, 61) etc.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%